[Zn4O] Cluster‐Based Metal‐Organic Frameworks as Catalysts for Conversion of CO21. Issue 5 (25th March 2019) - Qiao, Wanzhen; Song, Tianqun; Zhao, Bin
Summary of main observation and conclusion: One unique two‐dimensional (2D) Zn‐MOF Na[Zn1.5 (μ4 ‐O)(L)] n (1 ) was synthesized under hydrothermal conditions and characterized by single‐crystal X‐ray diffraction. Four Zn atoms are bridged through μ 4 ‐O to form [Zn4 O] clusters, which are further linked to form a 2D layer network through sharing Zn as vertexes.1 exhibits high thermal stability up to 280 °C and keeps stable in common solvents and water solutions with pH ranging from 1 to 13. The catalytic studies reveal that compound1 exhibits excellent catalytic activity for cycloaddition of CO2 with epoxides into cyclic carbonates under mild conditions. Furthermore, 1 demonstrates good generality in CO2 coupling reaction with extensive epoxides. Importantly, 1 can be reused for at least five times without significant reduction in catalytic ability. Abstract : One new two‐dimensional [Zn4 O] cluster‐based MOF can serve as an efficient and recyclable heterogeneous catalyst to catalyze CO2 coupling with epoxides into cyclic carbonates under mild conditions.